Central nervous system effects of 5-HT7 receptors: a potential target for neurodegenerative diseases - Alejandro Quintero-Villegas; Sergio Iván Valdés-Ferrer (BMC, 2022)
Abstract 5-HT7 receptors (5-HT7R) are the most recently identified among the family of serotonin receptors. Their role in health and disease, particularly as mediators of, and druggable targets for, neurodegenerative diseases, is incompletely understood. Unlike other serotonin receptors, for which abundant preclinical and clinical data evaluating their effect on neurodegenerative conditions exist, the available information on the role of the 5-HT7R receptor is limited. In this review, we describe the signaling pathways and cellular mechanisms implicated in the activation of the 5-HT7R; also, we analyze different mechanisms of neurodegeneration and the potential therapeutic implications of pharmacological interventions for 5-HT7R signaling.